PENGARUH EKSTRAK CENGKEH (Eugenia aromatica L.) TERHADAP KUNJUNGAN LALAT BUAH (Bactrocera dorsalis Hend.) - Andri, Miki; Jasmi, Jasmi; Zeswita, Armen Lusi (Pendidikan Biologi, 2013)
ABSTRACTBactrocera dorsalis is one of the flies that are very harmful for horticulture crops. Farmers usually use chemicals to control the flies, but the way this has a negative impact on the environment. So needed another way to use a more environmentally friendly attractants such as plants that contain methyl eugenol, such as clove (Eugenia aromatica L.). Based on these problems then do research on the effect of extracts of clove (Eugenia aromatica L.) Against Fruit Fly Bactrocera dorsalis Hend. visit. This research is experimental, with 4 treatments and 6 replications. The study was conducted from July to September 2013. Data from studies conducted with mixed analysis of variance (ANOVA) and the F value obtained is greater than F table, means treatment gives significant effect on the number of flies that enter the trap. So proceed with Test BNJ 5 %. From BNJ test shows that treatment A (1 ml), B (2 ml), and treatment C (3 ml) having the same effect on the number of fruit flies that enter the trap. While treatment D (4 ml) was able to make a lot more fruit flies trapped. It can be concluded that the higher dose of clove extract on the treatment given, the more potent for berkunjungnya fruit fly Bactrocera dorsalis in a trap.Â Â